PERANAN OLAHRAGA RENANG DALAM MENJAGA KEBUGARAN JASMANI DAN KESEHATAN TUBUH - Ahmad Syabaruddin; Jack Winar Sitopu; Kevin A Simanjuntak; Norisman Zega; Josua Aldi Kurniawan; Hendro Jaya Sitorus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Swimming is one of the most effective physical activities for improving physical fitness and maintaining overall health. This study aims to analyze the role of swimming in enhancing physical fitness and body health based on findings from previous studies. The research employed a literature review method by examining various scientific journals related to swimming activities, physical fitness, and health. The results indicate that swimming has a significant positive effect on improving cardiorespiratory capacity, muscle strength, flexibility, body balance, and mental health. Swimming activities have also been proven to increase VO₂Max levels, improve heart and lung function, and help reduce the risk of diseases associated with a sedentary lifestyle. Furthermore, regular swimming exercises can enhance body endurance, reduce stress, and promote healthy lifestyle habits among adolescents and the general population. Due to its low-impact nature and minimal risk of injury, swimming is considered a safe and effective sport for individuals of all age groups. Therefore, swimming can serve as an alternative physical activity that plays an important role in maintaining overall physical fitness and body health.